Dietary calcium and magnesium intake and risk for incident dementia: The Shanghai Aging Study - Jianfeng Luo; Chenbo Zhang; Qianhua Zhao; Wanqing Wu; Xiaoniu Liang; Zhenxu Xiao; James A. Mortimer; Amy R. Borenstein; Qi Dai; Ding Ding (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Calcium (Ca), magnesium (Mg), or the calcium to magnesium (Ca:Mg) ratio may affect the risk of dementia via complex mechanisms. The aim of this study was to evaluate the association of dietary Ca, Mg, and Ca:Mg ratio with dementia risk at the prospective phase of the Shanghai Aging Study. Methods We analyzed data from 1565 dementia‐free participants living in an urban community who had measurements of dietary Ca and Mg intake derived from a food frequency questionnaire at baseline and incident dementia during follow‐up. Results Over the 5‐year follow‐up, 162 (10.4%) participants were diagnosed with incident dementia by Diagnostic and Statistical Manual of Mental Disorders, 4th edition criteria. Participants with the lowest tertile of dietary Ca (<339.1 mg/day) and Mg (<202.1 mg/day) had the highest incidence rates of dementia (3.3/100 person‐years for Ca, 3.3/100 person‐years for Mg) compared to those with higher Ca and Mg intake. In the subgroup with Ca:Mg ratios ≤ 1.69, Mg intake >267.5 mg/day was related to an increased risk for dementia (adjusted hazard ratio: 3.97, 95% confidence interval: 1.29–12.25). Conclusions Our findings suggest that high dietary intake of Mg is associated with an increased risk of dementia mainly among older adults with low Ca:Mg intake ratios. Proper balance of Ca to Mg in the diet may be critical to the relationship between Mg intake and risk of dementia. Highlights Participants with the lowest tertile of dietary calcium (Ca) and magnesium (Mg) had the highest incidence rates of dementia. In the subgroup with Ca:Mg ratios ≤1.69, Mg intake >267.5 mg/day was related to an increased risk for dementia. Balance of Ca to Mg in diet may be critical to the relationship between Mg intake and risk of dementia.